Assessing the impact of gut microbiota and metabolic products on acute lung injury following intestinal ischemia-reperfusion injury: harmful or helpful? - Wang, Qiong; Yu, Zi-Hang; Nie, Liang; Wang, Fei-Xiang; Mu, Guo; Lu, Bin (Frontiers in Cellular and Infection Microbiology, 2024)
Ischemia-reperfusion injury (IRI) is a common and clinically significant form of tissue damage encountered in medical practice. This pathological process has been thoroughly investigated across a variety of clinical settings, including, but not limited to, sepsis, organ transplantation, shock, myocardial infarction, cerebral ischemia, and stroke. Intestinal IRI, in particular, is increasingly recognized as a significant clinical entity due to marked changes in the gut microbiota and their metabolic products, often described as the body’s “second genome.” These changes in intestinal IRI lead to profound alterations in the gut microbiota and their metabolic outputs, impacting not only the pathology of intestinal IRI itself but also influencing the function of other organs through various mechanisms. Notable among these are brain, liver, and kidney injuries, with acute lung injury being especially significant. This review seeks to explore in depth the roles and mechanisms of the gut microbiota and their metabolic products in the progression of acute lung injury initiated by intestinal IRI, aiming to provide a theoretical basis and directions for future research into the treatment of related conditions.